ANALISIS VISIBILITAS & SPASIAL DESAIN MASJID KELORAN, BUGISAN, MENGGUNAKAN SPACE SYNTAX - ABRAR, AULIA (Universitas Negeri Gorontalo, 2025)
Mosque design needs to pay attention to aspects of accessibility and visuality because both aspects affect the physical comfort and spiritual experience of worshipers. This research aims to analyze the spatial visibility and connectedness of spaces in Keloran Mosque, Bugisan, through the Space Syntax approach. The research method involved field observation and floor plan analysis, while the spatial data was processed using Depthmap software to produce spatial integration and isovist maps. Results show that areas with high levels of spatial connectivity support smooth movement and easy access to key spaces such as prayer and ablution areas. Conversely, some zones with low visibility can reduce visual comfort and spiritual engagement, particularly in areas far from the worship center. The shape of the dome roof contributes positively to the visual focus towards the mihrab. This research proves that the Space Syntax method is effective in understanding spatial dynamics in mosque design. Based on the findings, it is recommended that mosque designs pay more attention to visibility and spatial layout in order to improve accessibility for all worshipers, including people with disabilities